2022
DOI: 10.3390/agronomy12051070
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Rainfed Barley Genotypes under Different Tillage Systems in Highland Areas of Dryland Conditions

Abstract: Conservation agriculture (CA) is becoming increasingly attractive to farmers due to advantages such as lower production costs and less destruction of soil structures compared to the conventional tillage. The cultivars introduced for the conventional systems may not be suitable under CA environments, and newly adapted cultivars need to be developed. Accordingly, four separate field experiments were conducted over two cropping seasons (2018–2019 and 2019–2020) to study the agronomic performance of seven barley g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This is in agreement with the results reported on barley, wheat, chickpea, and lentil [41,42]. However, other research found the association between genotype and tillage system insignificant [43]. Thus, the existing interaction in our case can be explained by the high diversity that our plant material presents.…”
Section: Genotype × System Interaction and Effect Of Genotype On All ...supporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the results reported on barley, wheat, chickpea, and lentil [41,42]. However, other research found the association between genotype and tillage system insignificant [43]. Thus, the existing interaction in our case can be explained by the high diversity that our plant material presents.…”
Section: Genotype × System Interaction and Effect Of Genotype On All ...supporting
confidence: 93%
“…For the checks in this case, significant differences were observed for the number of grains, the number of primary and secondary branches, the plant height, and the relative water content, with a slight superiority in conventional seeding. Results showing superiority in conventional seeding were reported by Roohi et al [43], and this would explain that these genotypes have a strong adaptation to conventional seeding through these traits.…”
Section: Effect Of Tillage On Grain Yield and All Other Traitssupporting
confidence: 52%
“…Moreover, phytate has been reported as an antinutrient factor [ 16 ], antioxidant [ 17 ] and anticarcinogenic [ 18 ]. The protection of wheat plants from heat-induced oxidative damage during the reproductive phase has also been correlated with some antioxidants, such as flavonoids and phenols [ 19 , 20 ]. Wheat straw can be used as feedstock and for energy production, which could open new markets for improving the rural agriculture-based economy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the world, especially in developing countries, the cultivatable land for cereals and legumes has declined significantly. This and climate change and the enhanced demands of an increasing population for food and feed all threaten food security, national security, and human survival [2][3][4]. Application of chemical fertilizers is the most common agricultural practice to improve soil nutrients and subsequently increase crop yield.…”
Section: Introductionmentioning
confidence: 99%